Ecotourism Development Isyo Hill's Bird Watching, Nimbokrang District, Jayapura Regency, Papua Province - Ima Wandikbo; Ni Gst Nyoman Suci Murni; Gede Ginaya; Dewa Made Suria Antara; Raden Ayu Trisnayoni (International Journal of Green Tourism Research and Applications, 2025)
One of the tourist destinations that needs to be developed is the Isyo Hill's Bird Watching ecotourism in the Nimbokrang District, Jayapura Regency, Papua Province.  However, the rapid increasing number of tourism activities in Hill's Bird Watching has led to significant biodiversity loss and environmental degradation. This is largely due to the absence of structured development strategies and unsustainable tourism practices. Addressing these challenges is crucial to preserving the unique ecosystem of Isyo Hill and ensuring long-term benefits for local communities. This study aims to evaluate current ecotourism practices and propose sustainable development strategies tailored to Isyo Hill’s context, using an ecotourism development model based on Tourism Area Life Cycle (TALC). Data collection methods were carried out through interviews, observation, documentation studies and focus group discussions (FGD). Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the study showed that Isyo Hill's Bird Watching was at the Development stage. The development efforts are needed so that tourist destinations do not occur Decline phase. The researcher combines the principles of ecotourism with the Pentahelix concept, involving five elements, including government stakeholders, investors, academics, media, and the community, into a new concept as the basis for development to form an overview of the Isyo Hill's Bird Watching ecotourism development model in a sustainable manner. Researchers hope that with the establishment of this ecotourism development model it can be implemented in all tourist destinations in Jayapura Regency, Papua Province in an effort to develop a sustainable ecotourism.